2010
DOI: 10.1269/jrr.09094
|View full text |Cite
|
Sign up to set email alerts
|

The Modified High-Density Survival Assay is the Useful Tool to Predict the Effectiveness of Fractionated Radiation Exposure

Abstract: The high-density survival (HDS) assay was originally elaborated to assess cancer cell responses to therapeutic agents under the influence of intercellular communication. Here, we simplified the original HDS assay and studied its applicability for the detection of cellular radioresistance. We have recently defined clinically relevant radioresistant (CRR) cells, which continue to proliferate with daily exposure to 2 gray (Gy) of X-rays for more than 30 days in vitro. We established human CRR cell lines, HepG2-89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 14 publications
0
42
0
Order By: Relevance
“…In order to understand and conquer radioresistant tumors, we have established CRR cell lines. 20, 21 Profile of radiation-induced cell death under a microscope could be divided into two major types: cell death with apoptotic bodies and that lacking apoptotic bodies. We speculated that the latter was autophagic cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to understand and conquer radioresistant tumors, we have established CRR cell lines. 20, 21 Profile of radiation-induced cell death under a microscope could be divided into two major types: cell death with apoptotic bodies and that lacking apoptotic bodies. We speculated that the latter was autophagic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…20, 21 These cells continue to proliferate with daily exposure to 2 Gray (Gy) of X-rays for >30 days, which corresponds to the standard protocol of fractionated radiotherapy for cancer treatment. This study revealed that CRR cells were refractory to the induction of autophagy after irradiation and that facilitation of autophagy by rapamycin (RPM) abrogated the CRR phenotype.…”
mentioning
confidence: 99%
“…The modified high-density survival (HDS) assay was performed according to the method of Kuwahara et al (2010). Exponentially growing cells (5 × 10 5 ) were seeded in a 60 mm tissue culture dish (Asahi Techno Glass Co., LTD) and incubated in DMEM with 1% FBS for 48 h. The cells treated with various concentrations of IL-6 (0, 50, and 200 pg ml −1 ) were then exposed to 6 Gy of X-rays.…”
Section: Methodsmentioning
confidence: 99%
“…The HepG2-8960-R, HepG2-R, SAS-R and HeLa-R CRR cell lines were independently established from the parental HepG2, SAS and HeLa cell lines through a stepwise increase in X-ray dose exposure from 0.5 to 2 Gy/day [24]. The cells that continued to stably proliferate under exposure to 2 Gy/day of X-rays were defined as CRR cells.…”
Section: Cell Culturementioning
confidence: 99%